Frame-constructional verb classes change and theft verbs in English and German - Dux, Ryan (Constructional approaches to language ;, 2020)
"While verb classes are a mainstay of linguistic research, the field lacks consensus on precisely what constitutes a verb class. This book presents a novel approach to verb classes, employing a bottom-up, corpus-based methodology and combining key insights Frame Semantics, Construction Grammar, and Valency Grammar. On this approach, verb classes are formulated at varying granularity levels to adequately capture both the shared semantic and syntactic properties unifying verbs of a class and the idiosyncratic properties unique to individual verbs. In-depth analyses based on this approach shed light on the interrelations between verbs, frame-semantics, and constructions, and on the semantic richness and network organization of grammatical constructions. This approach is extended to a comparison of Change and Theft verbs, revealing unexpected lexical and syntactic differences across semantically distinct classes. Finally, a range of contrastive (German-English) analyses demonstrate how verb classes can inform the cross-linguistic comparison of verbs and constructions"--